Prediction of Breast Self-Examination Behavior Among Omani Undergraduate Students Using Champion's Health Belief Model - Lina Mohanmmed Wali Shakhman RN, BSN, MSN; Judie Arulappan RN, RM, MSN, PhD, DNSc (SAGE Publishing, 2023)
Introduction Breast cancer (BC) is a most common and frequently occurring malignancy of women worldwide. Breast self-examination (BSE) is important for the early detection and prevention of BC and to limit the morbidity and mortality. Young students are ideal people to understand and motivate other women to perform BSE. Objective BSE behavior of undergraduate students was predicted using Champion's Health Belief Model Scale (CHBMS). Methods A descriptive cross-sectional design was adopted. This study was conducted in all nine colleges of Sultan Qaboos University, , Oman. Three-hundred eighty-one female undergraduate students were selected through convenient sampling technique. The health belief towards BSE was predicted using CHBMS. Results The mean and SD of beliefs about the benefits of performing BSE showed 10.84 and 3.2, respectively. Mean and SD of confidence in performing BSE indicated 56.24 and 10.8. Likewise, the mean and SD of barriers in performing BSE are 13.58 and 4.2. Source of information is found to be a statistically significant predictor of barrier in performing BSE at p  < .05. Conclusion If the self- confidence of women in performing BSE improves, the women will uptake BSE more frequently thereby they can be prevented from developing the adverse consequences of advanced stages of breast cancer.